2019
DOI: 10.3390/f10121051
|View full text |Cite
|
Sign up to set email alerts
|

The Soil Microbiome of the Laurel Forest in Garajonay National Park (La Gomera, Canary Islands): Comparing Unburned and Burned Habitats after a Wildfire

Abstract: The evergreen laurel forest is a relic of ancient subtropical/tropical forests, of which the best remnant in the Canary Islands is in Garajonay National Park, on La Gomera island. The soil microbiome associated with a mature undisturbed (unburned) laurel forest was characterized at two locations at different topographical positions on the mountain: The slope and the ridge crest. Given the unusual circumstance of an intense wildfire that severely affected part of this forest, the burned soils were also studied.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 72 publications
3
6
0
Order By: Relevance
“…In line with the results reported in other forest ecosystems (e.g., [52,53]), Actinobacteria, Proteobacteria, and Acidobacteria were the most abundant phyla (Figure 1). Bacteria belonging to these phyla usually participate in C, N, and S cycles and are also responsible for the production of secondary metabolites associated with plant resistance to pathogens [54].…”
Section: Disentangling Changes In the Rhizosphere Community Structuresupporting
confidence: 90%
“…In line with the results reported in other forest ecosystems (e.g., [52,53]), Actinobacteria, Proteobacteria, and Acidobacteria were the most abundant phyla (Figure 1). Bacteria belonging to these phyla usually participate in C, N, and S cycles and are also responsible for the production of secondary metabolites associated with plant resistance to pathogens [54].…”
Section: Disentangling Changes In the Rhizosphere Community Structuresupporting
confidence: 90%
“…700–800 to ca. 300 OTUs) [ 68 ]. Thus, soil dynamics depend on a complex nexus of several factors, including anthropogenic and environmental parameters [ 27 , 69 , 70 ] that are probably site-specific.…”
Section: Resultsmentioning
confidence: 99%
“…These phyla are frequently reported in the soils of other forest ecosystems [ 9 , 68 , 76 , 77 ] comprising ubiquitous bacteria with a multiplicity of ecological functions such as soil fertilization, bioremediation and plant nutrition, growth, and protection [ 1 , 78 , 79 ]. In general, the bacterial variation patterns imposed by HFF followed the same trend in S and R soils, contrasting with O soils.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While our study did not directly measure soil microbiota, our observations correlate with those performed by microbiota surveys of burnt soils. In Villadas et al (2019), Dove et al (2022), and Pulido‐Chavez et al (2023), a swift reduction in diversity is typically observed immediately after a fire followed by a boost in taxonomic diversity that results from the release of pyrogenic nutrients. In our observations, salamander skin microbiota possessed a greater taxonomic diversity of bacterial phyla in burnt areas immediately after a wildfire (those sampled from burnt areas in 2021) compared to those sampled a few years after the last wildfire (those sampled from burnt areas in 2018).…”
Section: Discussionmentioning
confidence: 99%